Evaluation of the Effect of Income Level on Food Choices of Elementary School Students - Damla GÜMÜŞ; Mevlüde KIZIL; Derya DİKMEN; M. Fatih UYAR (Hacettepe University, 2015)
Objectives: The aim of this study was to evaluate the effect of income levels on students' food choices. Materials and Methods: The study was conducted on randomly selected 1429 students (47.8% boys, 52.2% girls) aged between 13-15 years in different elementary schools under the Provincial National Education Directorate of Ankara. Students' anthropometric measurements such as body weight, height were measured and according to these data, Body Mass Index (BMI) was calculated. Personal information of subjects, demo graphic status and food choices were obtained by a questionnaire using face to face interview. The results were evaluated statistically by using SPSS 22.0 statistical package program. Results: Income levels of students' parents below 1000 TL were 21.1% , between 1001-2000 were 24% , between 2001-3000 TL were 23.3% , between 3001-5000 TL were 19.6%, 5001 TL and above were 12.1%. Students' food choices in school canteens were investigated and it was found that fast food choice frequency of students increased as their parents' income levels increase (p<0.05). There was a positive correlation between parents' income levels and milk (plain, chocolate, fruit) choices of students (p<0.05). Frequency of snacks choices (such as biscuits and crackers) decreased as income levels of parents' increase. No significant difference was observed between nuts, chips, candy, sweet, chocolate, fruit juice, tea, coffee choices and income levels (p>0.05). Conclusion: Income level effects food choices of students in school canteens. Students should be informed about adequate and balanced nutrition in order to make healthy food choices and healthy food alternatives should be provided in school canteens